DEVELOPMENT TRENDS IN ASSET OPERATIONS OF COMMERCIAL BANKS - To‘ychiev Otabek Shamshievich (American Journals, 2025)
This study examines the development trends of commercial banks’ active operations in Uzbekistan, with a particular focus on the role of the National Bank. The analysis highlights the growing importance of credit operations, investment activities, and interbank placements in shaping the structure of banking assets. Special attention is given to the strategic measures undertaken to enhance human capital, including the establishment of corporate academies and large-scale investments in staff training, which improve institutional efficiency and align banking practices with international standards.
Keywords: Commercial banks, active operations, Uzbekistan, credit operations, investments, asset structure, financial stability, human capital, corporate academy, innovation, digital banking, IT systems, risk management, sustainable growth.